IMPACT OF CALCIUM, HOT WATER AND MODIFIED ATMOSPHERE TREATMENTS IN CHILLING INJURY SUSCEPTIBILITY OF STORED PAPAYAS - Korkar M. (Arab Universities Journal of Agricultural Sciences, 2016)
Mature-green solo papaya fruits with color index green with trace of yellow were subjected at 2014 and 2015 seasons to many pre storage treatments. CaCl2 5% solution  either  at ambient temperature or 45°C in combined with modified atmosphere package (MAP), hot water at 45°C with or without MAP and untreated fruits were investigated, comparing to commercial treatments . All treatments except treatments were cold stored at 5 for one or two weeks followed by 7 days at 18°C for marketing period, where commercial treatment was stored at 10 °C for two weeks and 7 days at 18°C. The obtained result were recorded at chilling injury symptoms , weight loss % , decay fruit % , fruit firmness (Kg\ f)., L- ascorbic acid content  T.S.S. ,acidity , salute leakage ethylene production with or without MAP were effective in minimizing orb prevent chilling injury symptoms of solo papaya fruits stored at 5 ±1°C followed marketing at 18±1°C. Storability and good quality and improved chemical characteristics of solo papayas were obtained with pre – storage treatments of solo papaya were obtained with pre – storage treatments compared with control or commercial treatment.